The city and the negro - Silberman, Charles E. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1962)
A solution to the negro problem demands difficult and heroic decisions on the part of civic and political leaders and changes in the behavior of Americans from every walk of life--teachers and students, trade-union leaders and members, and employers and employees. Current action being taken and future actions which need to be taken are discussed. The shame of slavery, the visual differences in race, and the lack of education and training in new technologically demanding times have made the problems of the negro difficult and self-perpetuating. Too many negroes are unable or unwilling to compete in an integrated society. Charitable and social-welfare programs organized, staffed, and supported by negroes are likely to have a much greater impact on negro behavior than programs administered by government or by private white agencies, both of which tend to be viewed with suspicion and hostility. To penetrate the environmental and cultural curtain that keeps the negro child from learning, the school should take on a comprehensive set of functions that lie outside its normal sphere. The negro child needs the same kind of education the white child needs--an education that gives him the intellectual discipline and depth of understanding that will enable him to meet new conditions as they arise. A new pride is self should be developed to help raise negro aspirations and achievements. This article is a reprint from "fortune magazine," March 1962.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Black Attitudes; De Facto Segregation; Equal Education; Equal Opportunities (Jobs); Essays; Housing Opportunities; Social Discrimination; Urban Problems; New York -- New York (New York)